Nội dung từ Loigiaihay.Com
Câu hỏi:
Gọi \(M = \cos x + \cos 2x + \cos 3x\) thì :
Phương pháp giải:
Sử dụng công thức \(\cos a + \cos b = 2\cos \dfrac{{a + b}}{2}\cos \dfrac{{a - b}}{2}\).
Lời giải chi tiết:
\(\begin{array}{l}\,\,\,\,\,\,M = \cos x + \cos 2x + \cos 3x \Leftrightarrow M = 2\cos 2x\cos x + \cos 2x\\ \Leftrightarrow M = \cos 2x\left( {2\cos x + 1} \right) \Leftrightarrow M = 2\cos 2x\left( {\cos x + \dfrac{1}{2}} \right)\\ \Leftrightarrow M = 2\cos 2x\left( {\cos x + \cos \dfrac{\pi }{3}} \right) \Leftrightarrow M = 2\cos 2x.2\cos \dfrac{{x + \dfrac{\pi }{3}}}{2}\cos \dfrac{{x - \dfrac{\pi }{3}}}{2}\\M = 4\cos 2x\cos \left( {\dfrac{x}{2} + \dfrac{\pi }{6}} \right)\cos \left( {\dfrac{x}{2} - \dfrac{\pi }{6}} \right)\end{array}\)
Chọn D.